An analysis of VDT monitor placement and daily hours of use for female bifocal users. - Lyon JL Jr.; Lillquist DR; Alder S; Stephenson D; Bloswick DS (Work, 2003)
A population of 72 bifocal wearers was studied to determine the relationship between VDT (video display terminal) placement for those who reported musculoskeletal pain and those who did not. The mean hours worked was 50.4 minutes (p=0.003) greater for those who reported head/neck pain versus those who did not and 48.6 minutes (p=0.004) greater for those who reported shoulder/arm pain that those who did not. There was no statistically significant difference between the means of monitor height, distance, or angle for those who reported pain symptoms versus those who did not. This study indicates that, self reported pain symptoms are correlated with hours of VDT work and that there appears to be a threshold at approximately five hours for pain symptoms among bifocal wearers. No such correlation can be made for monitor placement